Quem dá as cartas?: discursividade e retórica nas cartas de campanha eleitoral à Reitoria da UFMG em 2005 - Humberto Cesar Clemente Mendes (2008)
This survey aims to analyse the letters written by the candidates of the 2005 UFMG electoral campaign for Rector according to aspects of dicursivity and use of a theoretical framework for the construction of a political-scientific discourse. The theoretical principles of the Perelmansand Olbrechts-Tytecas New Rethoric (2005), the constitutive elements of the Rebouls (2004) and Amossys (2005) rethorical argument ethos, pathos and logos as well as Habermass (1990) concepts of strategic and communicative actions are considered. The aim of these choices is to demonstrate how the letters addressed to three segments of the universitarian community teachers, technical and clerical staffs, and students allow the identification of images that the candidates make of the academic community, and to propose a reflection on that electoralprocess, taking into account the indices of achieved votes. The results of the survey affirm the politicity of the academic discourse and reveal a preemption of the political debate, since fundamental issues regarding the universitarian community are taken as background ones.